A importância do teste funcional de software para a garantia de qualidade em sistemas de informação. - VIEIRA, Gabriela Fernandes; GIL, Rafael Augusto Silva (288, 2025)
Com o avanço da tecnologia e a digitalização dos serviços, a busca por softwares confiáveis e eficientes aumentou significativamente. Nesse contexto, os testes de software, especialmente os testes funcionais, se tornaram essenciais para garantir a qualidade dos sistemas de informação. Eles validam o comportamento do sistema conforme os requisitos definidos, sem considerar o código-fonte, contribuindo para a prevenção de falhas, redução de custos e aumento da confiança dos usuários. Sua aplicação é fundamental em setores críticos, onde a estabilidade e a segurança são prioridades. Diante do exposto o estudo tem como objetivo geral analisar a importância do teste funcional de software para garantir a qualidade em sistemas de informação. To this end, this study was developed through a case study, aiming to test the effectiveness of functional testing and to compile and analyze information already published by experts in the field. It is concluded, therefore, that functional testing is an indispensable tool for the development of quality systems, representing a competitive advantage for companies and professionals seeking excellence in their technological products and services.

With the advancement of technology and the digitalization of services, the search for reliable and efficient software has increased significantly. In this context, software testing, especially functional testing, has become essential to ensure the quality of information systems. It validates the behavior of the system according to the defined requirements, without considering the source code, contributing to the prevention of failures, cost reduction and increased user confidence. Its application is essential in critical sectors, where stability and security are priorities. Given the above, the main objective of this study is to analyze the importance of functional software testing in ensuring quality in information systems.
The importance of software functional testing for quality assurance in information systems.
Keywords: Desenvolvimento de software; Segurança de software; Informação - segurança; Informação e Comunicação